2011
DOI: 10.1055/s-0030-1259309
|View full text |Cite
|
Sign up to set email alerts
|

2-Substituted-2,3-dihydro-1H-quinolin-4-ones via Acid-Catalyzed Tandem Rupe Rearrangement-Donnelly-Farrell Ring Closure of 2-(3′-Hydroxy­propynyl)anilines

Abstract: A range of 2-substituted 2,3-dihydro-1H-quinolin-4-ones have been synthesized from anilines by a two-step process involving Sonogashira coupling with a propargyl alcohol then acid catalyzed cyclization of the resulting 2-(3'-hydroxypropynyl)anilines. The cyclization reaction appears to proceed via regioselective rearrangement of the propargyl alcohol to an -unsaturated ketone (Rupe rearrangement) and then 6-endo-trig ring-closure (Donnelly-Farrell cyclisation). The isolation of the -unsaturated ketone in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…The combined organic layers were washed with H 2 O (40 mL) and dried (MgSO 4 ). The evaporation of the solvent in vacuo gave the crude product 3(b-f) or 4-(2-aminophenyl)-2-methylbut-3-yn-2-ol (8) that was used without further purification (the 1 H and 19 F NMR spectra agreed with the literature data [11,12]). PTSA was added to the solution of crude 3(b-f) or 8 in AlkOH (25 mL), and the mixture was heated under reflux with stirring.…”
Section: 4 0 -(4-amino-6-fluoro-13-phenylene)bis(2-methylbut-3-yn-supporting
confidence: 68%
See 1 more Smart Citation
“…The combined organic layers were washed with H 2 O (40 mL) and dried (MgSO 4 ). The evaporation of the solvent in vacuo gave the crude product 3(b-f) or 4-(2-aminophenyl)-2-methylbut-3-yn-2-ol (8) that was used without further purification (the 1 H and 19 F NMR spectra agreed with the literature data [11,12]). PTSA was added to the solution of crude 3(b-f) or 8 in AlkOH (25 mL), and the mixture was heated under reflux with stirring.…”
Section: 4 0 -(4-amino-6-fluoro-13-phenylene)bis(2-methylbut-3-yn-supporting
confidence: 68%
“…On the first step, fluorinated o-iodoanilines 2(a-f) were cross-coupled with 2-methyl-3-butyn-2-ol in MeCN in the presence of Pd(PPh 3 ) 2 Cl 2 (4 mol %), CuI (9 mol%) and Et 3 N. Then, the prepared acetylene derivatives 3(a-f) were cyclized in boiling AlkOH (Alk = Me, Et, nBu) in the presence of PTSA as a catalyst to give 2,2-dimethyl-2,3-dihydro-1H-quinolin-4-ones 1(a-f) with good and excellent yields calculated for the two-step procedure (Scheme 1, Table 1). The acid-mediated cyclization is generally accepted to proceed via regioselective hydrative-dehydrative rearrangement of the alkyne moiety through intermediate 1-(2-aminophenyl)-3-methylbut-2-en-1-ones [10,11].…”
Section: The Synthesis Of Fluorinated 22-dimethyl-23-dihydro-1h-quimentioning
confidence: 99%
“…The 1 H NMR results, showed that the isomer 1 was the target product due to the appearance of a signal characteristic for the methyl group (C-4) at δ 2.69 ppm while in the isomer 6 the methyl proton appeared at δ 2.28 ppm. The 1 H NMR, 13 C NMR and HRMS results of compound 1 were in agreement with those reported in the literature. 8 Moreover, in the NOE difference experiments for the isomer 1 and 6 ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, for the trifluoro-substituted compounds 3c(ac) containing a fluorine atom in the o-position relative to the acetylene group, the reaction was always in favor of heterocyclization, even when performing the reaction in MeOH ( Entries 3,8,14). Moreover, the accumulation of the deactivating effect of the fluorine atoms was responsible for a significant increase of the time required for reaction completion: 62 h in the case 3cc even when using 2.5 times more catalyst.…”
mentioning
confidence: 99%